A Supply Chain Analysis of Incentive Travels: A Case of Thailand - chatchuda thumachai; Pimpika Chawalit; Warattaya Chinnakumj; Chukiat Chaiboonsri; Anuphak Saosaovaphak; Benjenop Buranasiri; Korawan Sangkakorn; Thiranun Khamhom; Pairach Piboonrungroj (International Journal of Supply Chain Management, 2017)
In this paper, we explored supply chain structures and characteristics of the incentive travel industry, which is a special sector of the tourism and hospitality industry. Since the conceptual framework tailor-made for this sector cannot be found, we developed a generic model to outline key players and main operations such as collaborations and relationships between players in the supply chain. Then we verified the model with empirical data collected from the incentive travel industry in Thailand. A focus group discussion was organised to validated and contextualise the proposed framework. Four followed up in-depth interviews with incentive supply chain players in Thailand were conducted. Data were cross-validated using various data sources including private sector, public sector and educational institutes. Findings show that the main players in incentive supply chain are the incentive houses, who plan and design the incentive programme for the corporate considering the return-on-investment (ROI), and destination management companies (DMC), who execute the programme at the destination. Relationships and collaboration between players are vital to the success of incentive program delivery since the incentive travel programmes are considered special events that required tailored made supplies and operations. Finally, potential research arena also discussed with suggested methods.